Case Report: The Value of Genomic Analysis in a Case of Megakaryoblastic Leukemia With Atypical Initial Manifestation - Gutiérrez-Jimeno, Miriam; Panizo-Morgado, Elena; Calvo-Imirizaldu, Marta; Galán-Gómez, Víctor; Escudero-López, Adela; Patiño-García, Ana (Frontiers in Pediatrics, 2022)
We report the case of a 7-month-old female patient who developed acute megakaryoblastic leukemia six months after the appearance of skull bone lesions. Initial evaluation and diagnosis of this patient were challenging and only achieved thanks to genomic analysis by NGS (next generation sequencing). It is unusual for the initial manifestation of acute megakaryoblastic leukemia to be a skull bone lesion. Extramedullary acute myeloid leukemia (eAML), also known as myeloid sarcoma (MS), often occurs simultaneously with acute myeloid leukemia (AML), although it may precede AML. Genomic analysis based on a NGS panel (Oncomine Childhood Cancer Research Assay) detected a RBM15::MKL1 fusion, a consequence of a t(1;22)(p13; q13) translocation, establishing the diagnosis of acute megakaryoblastic leukemia and enabling disease follow-up by qPCR. A diagnosis of eAML is built up from various findings in radiological, histological, immunophenotypic and genomic studies; when the tumor appears de novo, diagnosis is more complicated. We emphasize the importance of a multidisciplinary team in the initial approach to rare tumors and the use of genomic studies to contribute to the knowledge of these neoplasms, risk stratification and treatment planning